Maternal Floor Infarction: An old entity yet a finding not to be missed - Nur Syahrina Rahim; Nazifah Adznan; Kalavathy Ramachandram; Vickneswaran Ramasamy; Valyakalayil Daniel Philip; Abd Rahman Hayati (College of Pathologists, Academy of Medicine Malaysia, 2024)
The 2015 Annual Scientific Meeting of the College of Pathologists, Academy of Medicine Malaysia & 40th Anniversary Celebration of the Pathology Advocates was held at Berjaya Time Square Hotel, Kuala Lumpur from 13-14 June 2015.